Associations between regular physical exercise and physical, emotional, and cognitive health of older adults in China: an 8-year longitudinal study with propensity score matching - Xu, Xiaoyan; Zheng, Yawen; Fang, Juan; Huang, Jiahui; Yang, Xudong; Zhu, Xianghe; Liu, Yanlong; Chen, Li; Wu, Shaochang (Frontiers in Public Health, 2024)
Background The importance of healthy aging is growing in China as it has the largest number of older adults in the world and is one of the fastest-aging countries. This study aimed to examine the predictive value of regular physical exercise in relation to the physical, emotional, and cognitive health among samples of adults aged ≥60 years in China during an 8-year period. Methods A total of 10,691 older adults were extracted from two waves of national data from the China Family Panel Studies in 2010 and 2018. To minimize the impact of selection bias on the findings, a longitudinal propensity score matching (LPSM) method was used to examine the relationships between regular physical exercise and emotional health (depression), between regular physical exercise and physical health (instrumental activities of daily living), and between regular physical exercise and cognitive health (cognitive ability) of older adults. After LPSM, 856 older adults were included in the study. In the regular physical exercise group, the average age of participants at baseline year was 65.67 years, with an average age of 65.90 years for 238 men and 65.45 years for 190 women, and in the non-physical exercise group, their average age at baseline year was 65.70 years, with an average age of 65.45 years for 253 men and 65.98 years for 175 women. Results LPSM indicated that regular physical exercise has been found to be effective in improving physical function and reducing depressive symptoms in old adults, even after controlling for background differences. However, the sensitivity analysis suggests that the positive association between regular physical exercise and cognitive function may not be sufficiently valid. Conclusion The findings of this study indicate that engaging in long-term structured and repetitive physical exercise can have a significant positive effect on reducing depressive symptoms and improving the physical function of older adults. As a result, incorporating regular physical exercise into the lifestyle of older adults is recognized as an effective strategy for promoting healthy aging and reducing the strain on public health resources.